ADENOSINE DEAMINASE ACTIVITY AND SERUM C-REACTIVE PROTEIN AS PROGNOSTIC MARKERS OF CHAGAS DISEASE SEVERITY - BRAVO-TOBAR, Iván Darío; NELLO-PÉREZ, Carlota; FERNÁNDEZ, Alí; MOGOLLÓN, Nora; PÉREZ, Mary Carmen; VERDE, Juan; CONCEPCIÓN, Juan Luis; RODRIGUEZ-BONFANTE, Claudina; BONFANTE-CABARCAS, Rafael (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
Chagas disease is a public health problem worldwide. The availability of diagnostic tools to predict the development of chronic Chagas cardiomyopathy is crucial to reduce morbidity and mortality. Here we analyze the prognostic value of adenosine deaminase serum activity (ADA) and C-reactive protein serum levels (CRP) in chagasic individuals. One hundred and ten individuals, 28 healthy and 82 chagasic patients were divided according to disease severity in phase I (n = 35), II (n = 29), and III (n = 18). A complete medical history, 12-lead electrocardiogram, chest X-ray, and M-mode echocardiogram were performed on each individual. Diagnosis of Chagas disease was confirmed by ELISA and MABA using recombinant antigens; ADA was determined spectrophotometrically and CRP by ELISA. The results have shown that CRP and ADA increased linearly in relation to disease phase, CRP being significantly higher in phase III and ADA at all phases. Also, CRP and ADA were positively correlated with echocardiographic parameters of cardiac remodeling and with electrocardiographic abnormalities, and negatively with ejection fraction. CRP and ADA were higher in patients with cardiothoracic index ≥ 50%, while ADA was higher in patients with ventricular repolarization disturbances. Finally, CRP was positively correlated with ADA. In conclusion, ADA and CRP are prognostic markers of cardiac dysfunction and remodeling in Chagas disease.